Monis
6 год назад
Решить уравнение (3х-1)^3 = 27х^3-1
ОТВЕТЫ
Кириллович
Jun 30, 2019
27х^3-27х^2+9х-1^3=27х^3-1
-27х^2+9х=0
-9х•(3х-1)=0
х(3х-1)=0
х=0
3х-1=0
х=1/3
Ответ: х1=0; х2=1/3
-27х^2+9х=0
-9х•(3х-1)=0
х(3х-1)=0
х=0
3х-1=0
х=1/3
Ответ: х1=0; х2=1/3
Ответ:
(3x-1)^3=27x^3-1
27x^3-3*x^2*1+3*x*1^2-1^3=27x^3-1
27x^3-3x^2+3x-1=27x^3-1
27x^3-3x^2+3x-1-27x^3+1=0
-3x^2+3x=0 |*(-1)
3x^2-3x=0
3x(x-1)=0
3x=0
x1=0
x-1=0
x2=1
(3x-1)^3=27x^3-1
27x^3-3*x^2*1+3*x*1^2-1^3=27x^3-1
27x^3-3x^2+3x-1=27x^3-1
27x^3-3x^2+3x-1-27x^3+1=0
-3x^2+3x=0 |*(-1)
3x^2-3x=0
3x(x-1)=0
3x=0
x1=0
x-1=0
x2=1
277